Empirical vibration investigation of homogeneous ground with shallow tunnel by low-frequency excitation - Thu-Hang TRAN; Duc-Phong PHAM (Journal of Materials and Engineering Structures)
Urban tunnels and underground structures usually stay at small overburden heights. The insight of shallow underground structures' behaviours is challenging. Low-frequency seismic waves can create significant deformations to civil structures, so the prediction and warning of the damage possibility of a low-frequency earthquake to the civil infrastructure has attracted research attention. This paper presented an experimental investigation on a physical model including a homogeneous ground and a shallow tunnel. The model underwent an artificial harmony low-frequency excitation created by a 2x2m shaking table. The vibration characteristics of the model’s components were studied and discussed. The accelerograms and the FFT spectrum analysis was realised to understand the similarity of the input and output signals. The Cumulative Absolute Velocity and the Arias Intensity were determined and the correlation between them was investigated. The results proved the complexity of the vibration behaviours of the physical model during the artificial earthquake. The severe effect of the low-frequency excitation on the ground and underground structure motion was also detected.